THE SPECIAL OPINION OF THE JUDGE IN THE CIVIL PROCEEDINGS OF THE REPUBLIC OF KAZAKHSTAN (Journal of actual problems of jurisprudence, 2024)
The Civil Procedure Code of the Republic of Kazakhstan grants a judge, in a collegial vote, the right to express his disagreement with the majority of votes in writing on the issue of making a court decision. This right is considered by the theory of civil procedure law as a guarantee of compliance with the principle of freedom of evaluation of evidence. The general opinion is that disagreement is a condition for a judge to sign a decision with which he or she disagrees. These established positions are contradictory and require scientific analysis.The practice of recent years shows that when considering cases, judges increasingly rely on their own opinion, which differs from the majority. However, the legislator does not regulate the timing of the issuance of a special opinion of the judge and the procedure for familiarizing participants in the process with it. Although the judge's dissenting opinion does not directly have legal consequences, this system of civil proceedings is somehow related to various aspects of the legal system, such as regulating the status of a judge and organizing court proceedings (in particular, the availability of case materials to the parties, how to appeal court decisions, etc.). We believe that the judge's disagreement (or its absence) may indirectly affect the position of the court, the position of legislators in the public opinion system, the separation of branches of government and, in some cases, the development of law enforcement practice. In this article, the authors came to the conclusion that it is currently necessary to make changes and additions to the Civil Procedure Code of the Republic of Kazakhstan on the issue of a judge's dissenting opinion. According to the authors, in addition to increasing the transparency of judicial activities, the publication of a judge's dissenting opinion will help strengthen the principle of judicial independence and promote creative law enforcement.Keywords: court, judge, dissenting opinion, civil procedure, collegial composition of the court, court decision.